A critique of Marilyn Lake's Progressive New World. (September 2019) - Dabscheck, Braham
This review article provides a critique of Marilyn Lake's Progressive New World, a monograph that postulates that Australian/Australasian transpacific exchange shaped the development of American progressivism. The review outlines the major contours of her claim, notes her ambivalence concerning her overall position, and critiques her decision to not explain/examine differences in the political culture of the United States of America and Australia. The review seeks to overcome this problem by examining key differences in the cultural history of both societies and draws on the insights of Alexis de Tocqueville's Democracy and America . The review (a) develops a model which provides a means to understand how one society can impact another; (b) contrasts the origins of progressivism in the United States of America and Australia; (c) examines the work of the Australian scholar Michael Roe, who postulated that American progressivism was the independent factor impacting Australian developments; (d) distinguishes between two types of progressivism – racist conceit, pure and simple, and broader social reforms, which may or may not entrench racist conceit; and (e) examines various dimensions of progressivism which Marilyn Lake has used in developing her claim. JEL codes: B10, B22